2011
DOI: 10.1097/shk.0b013e318231ee2e
|View full text |Cite
|
Sign up to set email alerts
|

Increased Neutrophil Adenosine A3 Receptor Expression Is Associated With Hemorrhagic Shock and Injury Severity in Trauma Patients

Abstract: Hypertonic saline (HS) has been investigated as an immune modulator following hemorrhagic shock and sepsis. The neutrophil (PMN) response to HS is regulated by the release of ATP, which is converted to adenosine and activates adenosine receptors. Binding to A3 adenosine receptors promotes PMN activation and inhibition of A3 receptors improves the efficacy of HS resuscitation. A3 receptor expression of PMN has not been previously evaluated in injured patients. Methods Whole blood was obtained from 10 healthy v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…HS triggers cAMP/PKA signaling via autocrine purinergic signaling processes that involve the release of cellular ATP, hydrolysis of ATP to adenosine, and the activation of adenosine receptors that modulate PMN responses [35-38]. These autocrine feedback mechanisms involve several different subtypes of the nucleotide and adenosine receptor families, collectively termed purinergic receptors, that may influence apoptosis and other PMN responses [39-44]. …”
Section: Discussionmentioning
confidence: 99%
“…HS triggers cAMP/PKA signaling via autocrine purinergic signaling processes that involve the release of cellular ATP, hydrolysis of ATP to adenosine, and the activation of adenosine receptors that modulate PMN responses [35-38]. These autocrine feedback mechanisms involve several different subtypes of the nucleotide and adenosine receptor families, collectively termed purinergic receptors, that may influence apoptosis and other PMN responses [39-44]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that still unknown purinergic signaling events triggered by trauma and HS could be reasons for the lack of clinical efficacy of HS resuscitation. As an example, we recently found that trauma causes a dramatic increase in A3 adenosine receptor expression by neutrophils [35]. A3 receptors have a co-stimulatory role in neutrophil activation by counteracting the anti-inflammatory effect of A2a receptors [18].…”
Section: Discussionmentioning
confidence: 99%
“…This was demonstrated by the fact that in formyl-peptide receptor 1 knockout mice (Fpr1 À/À ), neutrophils migrated to within 150 mm of the necrotic site (via CXCR2 mediated signalling) but failed to migrate to the area of injury [86]. Interestingly, it has recently been shown that blunt/penetrating injury and severe TBI leads to the up-regulation of the A3 adenosine receptor on the surface of circulating human neutrophils, and that the level of expression of this receptor correlated positively with patient injury severity score [87]. Since ATP is released upon tissue damage, the up-regulation of A3 receptor expression may be one mechanism underlying the heightened activation status of circulating neutrophils from trauma patients.…”
Section: Mitochondrial Dampsmentioning
confidence: 96%